Patient communication as the missing item in clinical nursing education: A qualitative content analysis study - Mahdieh Poodineh Moghadam; Ahmad Nasiri; Gholamhossein Mahmoudirad (Journal of Education and Health Promotion)
Background: One of the basic goals of nursing education is to upgrade students’ patient communication skills. In this regard, students’ experiences in relationships with patients can be the cornerstone of their knowledge. Therefore, the present study’s objective was to divulge nursing students’ experiences in communicating with patients during their study course. Materials and Methods: The qualitative method used in this research involved conventional content analysis. The study participants were nursing students, both undergraduate and graduate, in Iran who were selected through purposeful sampling. The research took place in 2022 at the hospital or the nursing and midwifery faculty of the Birjand University of Medical Sciences. In total, 12 interviews were conducted until data saturation was reached. The interviews were carried out in clinical settings as per the students’ preferences, where they interacted with patients. Each interview lasted 45–60 minutes, typically in one or two sessions. Results: Data analysis resulted in the extraction of 37 subcategories, 10 categories, and five themes. All the concepts that emerged during conventional content analysis revolved around nursing students’ experiences and were in line with the study’s objectives. The themes included sustainability of communication, divergent communication, communicational modeling, patient communication as the missing component of clinical nursing education, and communication as the essence of care. Conclusion: It is necessary to pay special attention to and enrich nursing educational curricula with patient communication courses and play the role of appropriate communicational models that can help greatly promote the health of patients.